Erosion : how land forms, how it changes - Stille, Darlene R. (Minneapolis, MN : Compass Point Books, 2005)
Describes the power and process of erosion, looks at erosion caused by water, wind, and glaciers, and examines what is being done to control erosion.
The power of erosion -- The erosion process -- How does water cause erosion? -- How does wind cause erosion? -- How can a glacier cause erosion? -- Controlling erosion.
Includes bibliographical references (p. 47) and index.
Library Media Connection
Science Books & Films (A.A.A.S.)
Wilson's Junior High School
7.9
5-8.
Keywords: Erosion -- Juvenile literature; Erosion; Erosion